Analysis Of the Effect Of Profitability And Public Ownership On Firm Value with Firm Size as A Moderating Variable In The Banking Industry Listed on The Indonesia Stock Exchange In The Period 2019-2022 - Duma Megaria Elisabeth; Elisabeth, Duma Megaria; Siahaan, Septony B; Silitonga, Ivo Maelina; Sagala, Farida; Simanjuntak, Gracesiela Y (Jurnal Ilmiah Accusi, 2025)
This research aims to examine the effect of profitability and public ownership on firm value with firm size as a moderating variable on the Indonesia Stock Exchange (IDX). The type of data used in this research is secondary data in the form of annual financial reports from companies listed on the Indonesia Stock Exchange (IDX). The data analysis method used multiple linear regression and Moderated Regression Analysis (MRA). The population of this research consists of 44 banking sector companies listed on the Indonesia Stock Exchange (IDX), with 11 companies selected as samples using purposive sampling method based on specific criteria. The data obtained was then processed using SPSS version 26 analysis tool. The results of the t-test show that profitability variable has a negative but insignificant effect on firm value (PBV), and public ownership variable has a significant negative effect on firm value (PBV). The results of the simultaneous test (F test) show that profitability (ROA) and public ownership (KP) together have a significant effect on price to book value (PBV). The moderation test results indicate that firm size strengthens the effect of profitability on firm value, but is unable to moderate the effect of public ownership on firm value. The results of this study also show that the independent variables are able to explain 31.7% of the PBV variable, while the remaining 68.3% is influenced by other variables outside this research model